تأثير التغيير التكنولوجي على تبني مفهوم المسؤولية البيئية - هبول الزهراء رحيل; بورنان إبراهيم (جامعة عمار ثليجي الاغواط, 2022)
The research problem revolves around knowing the extent of the impact of technological change on the adoption of the concept of environmental responsibility , which has become a focus especially recently due to the escalation of environmental pollution and neglect of the aspect related to environmental protection and its various elements that will not be in the interest of any institution, and it is a real bet to ensure survival and continuity. Reliance on environmental management systems within the enterprise will not only give it efficiency and effectiveness to meet the environmental challenges, but also the proactive element that enables it to achieve a competitive advantage, which in turn serves the economic interest of the enterprise and in conjunction with this reducing the environmental pollution resulting from the activity of these industrial enterprises. As for the case study , Sonatrach took an example . The results of the research showed that the latter is committed to keeping pace with technological change in the aspect of environmental protection , similar to agreements , international laws and legislation on environmental protection , environmental management and alternative energy for hydrocarbons.